An empirical analysis of supply chain finance adoption - Wuttke, David A.; Rosenzweig, Eve D.; Heese, Hans Sebastian (Journal of Operations Management, 2019)
Abstract Supply chain finance (SCF) makes the funding of the supply chain more efficient because it extends the financial strengths of buyers to their suppliers. Nevertheless, buyers sometimes struggle to persuade suppliers to adopt SCF quickly. To craft more effective supplier onboarding strategies, buyers need to know which suppliers are likely to adopt SCF faster. Drawing on the theoretical perspective on organizational motivation, we develop a research framework that uncovers the key drivers of supplier adoption speed. Our framework combines efficiency motive drivers, identified by recent analytical studies on SCF, with legitimacy motive drivers, which stem from a supplier's institutional environment and are new to the SCF literature. We test our hypotheses using a unique data set from a leading financial technology platform provider. We find that suppliers with more limited access to financing tend to adopt SCF faster. In addition, suppliers adopt SCF faster if such adoption is associated with more pronounced reductions in their financing costs. Legitimacy motive drivers also impact supplier adoption speed. Specifically, our results suggest that mimetic and normative pressures accelerate the speed at which suppliers adopt SCF, while coercive pressures seem to have such an effect only when the buyer's stakes are high.